Role of cardioprotective agents on chemotherapy-induced heart failure: A systematic review and network meta-analysis of randomized controlled trials. (January 2020) - Li, Xinye; Li, Yanda; Zhang, Tiansong; Xiong, Xingjiang; Liu, Nian; Pang, Bing; Ruan, Yanfei; Gao, Yonghong; Shang, Hongcai; Xing, Yanwei
Graphical abstract: Abstract: Background: Although previous clinical randomized controlled trials (RCTs) have tested the effect of a variety of cardioprotective agents on cancer therapy-induced cardiotoxicity, the number of included patients was limited, and the results remained controversial. In this study, we aimed to evaluate the preventive or therapeutic effects of cardioprotective agents on heart failure (HF) caused by cardiotoxicity induced by cancer therapy. Methods: We included trials of the following cardioprotective drugs: Angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, beta-blockers, aldosterone antagonists and stains. We extracted the relevant information with predefined data extraction forms, and assessed the risk of bias in randomized controlled trials with the Cochrane risk of bias tool. The primary outcome was the left ventricular ejection fraction of patients after chemotherapy. We used the random-effects model to carry out pair-wise meta-analysis, and then carry out the random-effects network meta-analysis within the Bayesian framework. Results: Twenty-two relevant RCTs, including 1 916 patients (79.6 % women) with a mean age of 48.4 years, were included. Based on the evaluation of all drug species from 20 studies (26 comparisons), the analysis found that 4 therapies, aldosterone antagonists (MD, 12.78 [95 % CI, 2.87–22.69] and MD, 13.75 [95 % CI, 2.21–25.30]), ACEIs (MD, 6.79 [95 % CI, 2.11–11.48] and MD, 7.76 [95 % CI, 2.64–12.88]), statin (MD, 8.35 [95 % CI, 1.11–15.59]), and beta-blockers (MD, 4.00 [95 % CI, 0.87–7.14]), had a higher efficacy than placebo and/or control, suggesting an LVEF protective effect of cardioprotective therapy. In the analysis classified by single drug or drug combination, based on 22 studies (31 comparisons), spironolactone (MD, 12.77 [95 % CI, 1.76–23.79] and MD, 14.62 [95 % CI, 1.70–27.55]), a combination of candesartan and carvedilol (MD, 12.40 [95 % CI, 0.99–23.81]), enalapril (MD, 7.35 [95 % CI, 1.16–13.54] and MD, 9.20 [95 % CI, 2.61–15.79]), and statin (MD, 8.36 [95 % CI, 0.36–16.36]) showed significant benefits in protecting left ventricular (LV) systolic function compared with the placebo and/or control. Conclusion: When classified according to drug type, aldosterone antagonists, ACEIs, statins, and beta-blockers could substantially improve the LV systolic function. In the analysis classified by single drug or drug combination, spironolactone, enalapril, and statin have a significant cardioprotective effect. However, ARBs have no cardioprotective effect and fail to improve the LVEF.